A systematic review of the relationship between social participation and psychological factors in social media among youth - Changning, Ren; Ahmad Ghazali, Akmar Hayati; Kamarudin, Syafila (Human Resource Management Academic Research Society (HRMARS), 2023)
With the popularity of Internet technology, social media came into being. Social media is becoming a new generation of social communication and is widely used by youth. Systematic reviews of youth use of social media have been limited, focusing almost exclusively on mental health and social interaction, and this paper aims to systematical analyze the existing literature focusing on existing research on youth social participation and mental health links. This study was guided by the PRISMA statement (preferred reporting item for systematic reviews and Meta-analyses), as this research methodology better addressed the clues to the youth social media research landscape. Based on a systematic review by Scopus and ScienceDirect, 29 articles were selected from 200 related articles. A review of these texts reveals 7 themes: social interaction, education, access to health information, youth language, subculture, political participation, and mental health. These seven themes further give rise to a total of 14 sub-themes. Future research suggests that social participation's influence on youth psychological changes can be better clarified. Therefore, the research on youth social participation is significant to youth mental health in social media.